Surveillance and characterization of Candida bloodstream infections in a Serbian tertiary care hospital - Predrag Stojanovic; Nikola Stojanovic; Zorica Stojanovic-Radic; Valentina Arsić Arsenijević; Suzana Otasevic; Pavle Randjelovic; Niko S Radulović (Journal of Infection in Developing Countries)
Introduction: Candida spp. frequently cause hospital-acquired bloodstream infections (BSI) with a high mortality rate (up to 70%). We analyzed the frequency, infection characteristics, potential predisposing factors, susceptibility to antifungal drugs, biofilm production and other virulence characteristics of Candida spp. isolates obtained from a tertiary care hospital in Niš, Serbia, during a one year period.